WORD FORMATION IN FACEBOOK CONVERSATION; A STUDY AT A GROUP PRODI ENGLISH DEPARTMENT FKIP UNIVERSITY MUHAMMADIYAH OF MATARAM IN ACADEMIC YEAR 2015-2016 - Asbah Asbah (Linguistics and ELT Journal, 2017)
This study was aimed at finding out “ Word Formation In Facebook Conversation; A Study At A Group Prodi English Department FKIP University Muhammadiyah of Mataram In Academic Year 2015-2016 ”. The method of this research is qualitative research was using case study, the participant of this research is a Group Prodi English Department FKIP University Muhammadiyah of Mataram, for five months from January to May the total was followed in Facebook conversation was three persons (teachers), and the whole of students were 20 persons. The instruments for collecting the data by using note taking. To analyze the data, the researcher classified word formation produced, and then the researcher analyzing the data. Based on this research it showed that there was 7words formation on facebook conversation in a Group Prodi English Department FKIP University Muhammadiyah of Mataram, consist of 1 Coinage, 5 of Blending, 5 of Clipping, 1 of Back- Formation, 7 of Reduplication, 1 of Compounding, 15 of Acronym. So the total word formation for all of the data was 35 data, which was used on a Facebook conversation in a Group Prodi English Department FKIP University Muhammadiyah of Mataram. The dominant type of word formation process that occurs on facebook conversation, in a Group Prodi English Department FKIP University Muhammadiyah of Mataram was Acronym, which is 15 data.